ANALISIS VEGETASI PADA HABITAT ORANGUTAN DI HUTAN HAUR GADING KABUPATEN HULU SUNGAI UTARA KALIMANTAN SELATAN - Abdus Samad; Abdi Fithria; Setia Budi Peran (Universitas Lambung Mangkurat, 2020)
This study aims to Analyze the Vegetation Condition of Orangutan Habitat in Haur Gading Forest, Hulu Sungai Utara Regency, Sorth Kalimantan. Methods undertaken, namely the analysis of the vegetation. This research shows the composition of the existing species on site research has 15 species so that the poor can be said to be a species of vegetation. The condition of the forest area of research is the area of swamp forest located on the banks of the river and the species of vegetation on the lower growth was dominated by rivals, the kelakai, and purun guava bird because it has a value of IVI (%) most high. While the species of vegetation on growth poles and trees dominated by species docked and wawangun because it has a value of IVI (%) most high. On site research has a low species of diversity because at the level of the pole and the tree has a very low species diversity < 1 and on the growth rate and for a stake has a diversity of species of lower > 1. Minimum Life Value (NKM) on any growth in say.Keywords: Important Value Index (IVI); Diversity Of Types; Minimum Life Value(NKM